(untitled) (Development Service Industry Management, 2025)
The article presents a comprehensive study of the transformations occurring in Ukraine’s domestic agri-food market under the influence of digitalization, geopolitical shifts, and logistical challenges. Against the backdrop of military conflict, disruption of traditional distribution channels, the breakdown of export-import chains, and changes in consumer behavior, online trade in agricultural products has emerged as a critical factor in ensuring food security and enhancing the adaptability of the agricultural sector. The role of e-commerce is identified as a tool for direct sales, minimizing intermediary chains and enabling farmers to interact directly with end consumers. The article analyzes new formats of digital agri-markets, including agricultural marketplaces, direct-to-consumer platforms, mobile applications, integrated logistics services, and CRM systems. Special attention is given to the logistical support of online trade, including delivery organization, cost structure, the implementation of smart technologies (GPS, IoT, artificial intelligence), and the development of local logistics hubs within territorial communities. A classification of digital distribution models is provided based on scalability, adaptability to regional conditions, and the level of digital integration. The study synthesizes positive international experiences in the development of agri-e-commerce (USA, the Netherlands, India), particularly the use of blockchain solutions, automated warehouses, smart delivery systems, and dynamic pricing algorithms. The practical experience of Ukrainian companies (AgroMarket, Zakaz.ua, FoodKit, Foodex24, DrovaEda) in the field of electronic trade in agricultural products is analyzed. Key barriers are identified, including the lack of logistics infrastructure at the community level, uneven digital literacy among farmers, and the low adaptability of some producers to modern distribution channels. The article substantiates the need to develop innovative logistics for the agricultural sector, particularly through the implementation of regional digital education programs, incentives for establishing distribution centers, subsidies for logistics costs, and state-level institutional support for the creation of digital platforms. In summary, modern models of online agricultural trade contribute to market decentralization, increased economic self-sufficiency of farming enterprises, shorter logistics chains, and reduced food losses. In the long term, the digital transformation of logistics and trade is poised to become a driver of domestic market recovery, the revitalization of rural areas, and the integration of Ukraine’s agro-industrial complex into global digital value chains.